FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN INDUSTRI KECIL DI KOTA PEKANBARU (STUDI KASUS AIR MINUM ISI ULANG) - Ester Simatupang; Denny Setiawan; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine how much influence of income,household members and price of demand refill drinking water in Pekanbaru city. This data collection was conducted in of Maret 2018. This study uses primary data obtained directly from the object of research, that is data collected from household users of refill drinking water in Pekanbaru city. The sampling technique using Convinience Sampling. Sample in this research were 100 of 247.234 the population household in Pekanbaru city. Data collection is done by using questionnaires and interview. Data analysis method used in this research use multiple linear regression.From the result of research indicate that the household members have a significant positive effect to demand of refill drinking water. While income and price have no significant to demand of refill drinking water. Based on the coefficient f determination (R2) obtained value of 0,353%. This shows that all independent variables affect the dependent variable 35,3%, while the remaining 64,7% is influenced by other variables not examined in this study.Keyword : Demand, Small Industries, Income, Household members, and Price